Psychological Dimension and Relevance of Nigerian Educational Policies: Parent’s Perceptual Approach - Tony Ganagana (Randwick International of Education and Linguistics Science Journal, 2021)
The paper explored the depth of psychological content that can be found in the Nigerian educational policies formulated over the years, and its relationship with their relevance to the needs of the people. To ascertain this parental responses of how they perceived the effectiveness of each of the educational policies they have witnessed from the colonial days to the presence were obtained. Parents who were between 55 years and 80 years were used in the study. Sample size was three thousand, two hundred and sixteen parents. They were to complete a rating scale entitled Educational Policy Psychological Rating Scale (EPPRS). Reliability coefficient of the instrument was 0.76. Being historical in design, data was analyzed with descriptive statistics. Findings revealed that the psychological contents (dimensions) of all the educational policies formulated so far in the country was low (Mean points < 50) and that the Pre-independence Educational Policy had the highest psychological elements (MP > 50). The psychological dimension as provided for in most of the Nigerian educational policies is grossly inadequate for policy effectiveness. It was further discovered that those educational policies that possessed low psychological background (dimension) also had lowered degree of relevance in addressing the needs of the people. Since psychological dimensions closely impinges on policy relevance, it was recommended among others that one of the emphases in developing educational policy is the provision of a rich psychological background in the policy.